2015
DOI: 10.3109/00365521.2015.1083050
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endoscopic ultrasonography and endoscopic ultrasonography-guided fine-needle aspiration for the diagnosis and grading of pancreatic neuroendocrine tumors

Abstract: EUS and EUS-FNA are highly sensitive and accurate diagnostic methods for pNET. Characteristic EUS findings such as large tumor size and MPD obstruction are suggestive of G2/G3 tumors and would be helpful for grading pNETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 25 publications
2
70
2
Order By: Relevance
“…From a clinical point of view, a size of >20 mm is considered the cut-off towards a more aggressive lesion. On the other hand, in the study by Fujimori et al [2], EUS G2 and G3 tumours were larger and more heterogeneous than G1 tumours.…”
Section: Progression-free Survivalmentioning
confidence: 86%
See 3 more Smart Citations
“…From a clinical point of view, a size of >20 mm is considered the cut-off towards a more aggressive lesion. On the other hand, in the study by Fujimori et al [2], EUS G2 and G3 tumours were larger and more heterogeneous than G1 tumours.…”
Section: Progression-free Survivalmentioning
confidence: 86%
“…This is also largely described in the recent literature [2,15,16,[21][22][23][24] and seems to be due to tumour heterogeneity. Yang et al [25], studying tumour heterogeneity on 45 liver metastases from pNETs, showed that G1 tumours are relatively homogeneous, whereas 91% of their G2 cases harboured areas with <3% Ki67-LI.…”
Section: Progression-free Survivalmentioning
confidence: 98%
See 2 more Smart Citations
“…The detection rate was 86% (range 75-97) in 9 studies comprising 220 patients [9,62,63,66,[70][71][72][73][74] .…”
Section: Sensitivity Specificity and Detection Ratesmentioning
confidence: 99%